Managing diversity in corporate America : an exploratory analysis - Marquis, Jefferson P.; Lim, Nelson; Scott, Lynn M.; Harrell, Margaret C.; Kavanagh, Jennifer, 1981-; Labor and Population Program; Rand Corporation (Santa Monica, CA : RAND, 2007)
Managing diversity has become a primary concern of top U.S. corporations. In this paper, the authors develop a fact-based approach to modeling diversity management. They use the model to determine whether diversity-friendly corporations really do stand out from other companies by analyzing the strategies pursued by 14 large U.S. companies recognized for their diversity or human resource (HR) achievements. Finally, to understand whether best practices alone make a company diversity-friendly, they compare a number of characteristics of best diversity companies, best HR companies, and other companies, using quantitative and qualitative methods. They find that firms recognized for diversity are distinguished by a core set of motives and practices that resemble those presented in the best-practices literature, but that best practices per se may not enable a company to achieve a high level of diversity. Contextual factors, such as industry affiliation and company size, may be as significant as strategic factors in influencing the extent of a company's diversity.
Introduction - The diversity management literature - Does the diversity literature hold up in practice? - Are best practices enough? -- Conclusion - Appendix A: Fortune's criteria for the "Best Companies for Minorities" - Appendix B: Diversity manager interview protocol.
"RAND Labor and Population."
"This paper is the final product of an Independent Research and Development (IR&D) project on best practices in corporate diversity management and results from the RAND Corporation's continuing program of self-initiated research"--Preface.
Includes bibliographical references (p. 33-34).
Also available on the internet via WWW in PDF format.
Description based on print version record.
Keywords: Corporate culture; Diversity in the workplace -- United States -- Management; Organizational effectiveness -- Social aspects